THE ART OF TATAH SUNGGING WAYANG AS A STRENGTHENING BRANDING COMMUNITY OF WAYANG PURWA CRAFTSMEN ASSOCIATION IN WAYANG GENDENG HAMLET, BANGUNJIWO BANTUL-YOGYAKARTA - Susanto, Moh. Rusnoto; Mariah, Siti; Lukitaningsih, Ambar; Surono, Sugiyarto; Saidon, Hasnul Jamal; Azizan, Ahamad Tarmizi; Dina Arumsari, Mela; Ahmad, Fandy; Wiwit, Ilma; Lianti, Desi; Pangestu, Raka; Bilqisa, Nazla H.; Maulidya, Thasya Alwa; Rismawati, Dewi; Khotimah, Kusnul (International Journal of Engagement and Empowerment (IJE2), 2024)
Gendeng Hamlet in Bangunjiwo Bantul is a hamlet where puppet craftsmen grow as one of the oldest craft centers in Bangunjiwo. Gendeng Hamlet, as a puppet craftsman, once experienced a heyday in the era of President Soeharto and continues to survive amid the times. The puppet artisans of Gendeng Bangunjiwo Hamlet over time, with assistance from akadfemisi and various servants from 1various agencies and ministries until now. The artisans continue to survive and consistently maintain the tradition of Javanese puppet inlay and try to restore the golden age by supporting the existence of the Gendeng Leather Puppet Craft Center with improved product quality. The method determined to implement PM UPUD community service is collaborative and participatory. The stages of implementation are as follows: stages or steps in implementing the solutions offered to overcome the problems of target partners. Describe the method of implementing community service each year, at least containing the following: Socialization, Training, Technology implementation, Mentoring and evaluation, and Sustainability Program. The program outputs obtained include: (1) Increasing the capacity of superior products, up-skilling creative human resources, and planning transfers. The flagship product of the Tatah Sungging Gendeng Craft Center is shadow puppets. More specifically, Yogyakarta style wayang kulit. Puppet artisans in Gendeng hamlet can make high-quality works—Puppet Patterning Application Technology & Application of Machine Learning, and Strengthening Branding. (2) Gendeng's leather puppets could penetrate foreign markets during its heyday. In the archipelago itself, especially Yogya and surrounding areas, gender leather puppets dominate the market. The wayang production of Gendeng has yet to be able to repeat its former glory period